The Impact Of Job Hopping On Career Development Of The Millenial Generation - Leovani, Ega (Jurnal Keuangan dan Bisnis, 2022)
This study aims to determine the effect of job hopping on career development in the millennial generation in the city of Pelembang. The population in this study are employees of the millennial generation. The sample used was 95 respondents using purposive sampling technique. The data analysis technique used is simple regression, used to predict the effect of job hopping on the career development of the millennial generation. In this study, data collection techniques were carried out using a questionnaire. The results showed that job hopping had an effect on the career development of millennial generation employees in the city of Palembang.